1986
DOI: 10.1177/0734371x8600600304
|View full text |Cite
|
Sign up to set email alerts
|

Reward Expectancies and Other Work-Related Attitudes in Public and Private Organizations: a Review and Extension

Abstract: In recent years numerous studies have compared such work-related attitudes of employees of public and private organizations as work satisfaction, organizational commitment, and perceived relations between performance and rewards ("reward expectancies"). These comparisons are rele vant to various theoretical and institutional design issues, including civil service reform. This paper reviews these studies and discusses problems in methodology and in the aggregation of findings in this area of research. It then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
0
24
1
Order By: Relevance
“…A comparison of the level of EOC with that reported in Su et al (2009) revealed that the level of EOC in the public sector is now on par with the level of EOC reported in the private sector, although it is noted that Su et al (2009) was conducted in the manufacturing industry. These findings conflict with the results found in previous studies (Buchanan 1974(Buchanan , 1975Rainey et al 1986;Balfour and Wechsler 1990;Zeffane 1994) and suggest that the level of EOC in public sector organizations has increased. The results support the findings of Morehead, Steel, Alexander, Stephen and Duffin (1997) who suggested that public sector organization employees exhibit higher levels of effort following the implementation of NPM initiatives.…”
Section: Conclusion and Discussioncontrasting
confidence: 84%
“…A comparison of the level of EOC with that reported in Su et al (2009) revealed that the level of EOC in the public sector is now on par with the level of EOC reported in the private sector, although it is noted that Su et al (2009) was conducted in the manufacturing industry. These findings conflict with the results found in previous studies (Buchanan 1974(Buchanan , 1975Rainey et al 1986;Balfour and Wechsler 1990;Zeffane 1994) and suggest that the level of EOC in public sector organizations has increased. The results support the findings of Morehead, Steel, Alexander, Stephen and Duffin (1997) who suggested that public sector organization employees exhibit higher levels of effort following the implementation of NPM initiatives.…”
Section: Conclusion and Discussioncontrasting
confidence: 84%
“…More specifically, one driving force behind this finding is likely the nature of the promotion processes in the two types of organizations. They are inherently different between public and private organizations (Rainey, 1979;Rainey, 1983;Rainey et al, 1986). Yet, we acknowledge that this distinction could also be attributable to differences in the frequency of telecommuting and the nature of the industries and job tasks for the organizations in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…These same government managers also felt constrained by formal personnel procedures in that these procedures made it more difficult to associate such incentives with performance. Managers in private industry did not feel similarly constrained (Rainey, 1979;Rainey, 1983;Rainey, Traut, & Blunt, 1986). Assuming these findings are representative of a public-private distinction, if public employees have more formalized processes for promotions and the like, then being on-site and in-sight may influence organizational reward outcomes less in public organizations than in private ones.…”
Section: Public Versus Privatementioning
confidence: 95%
“…An analysis of the literature on loyalty differences between the public and private sectors by Rainey, Trout, and Blunt (1985) found somewhat lower levels of work commitment among higher level government employees. Other research traced morale problems to a lack of recognition of public sector achievements, program cutbacks, Congressional failure to appropriate money for merit pay and bonuses, and the perception that political and personal considerations mostly determined individualized pay increases (U.S. Office of Personnel Management, 1980;Romzek and Hendricks, 1982;Rosen 1983;Pearce and Perry,.…”
Section: The Issuementioning
confidence: 96%